Life‐table analyses for the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae): effects of plant genotype. Issue 6 (13th February 2023) - Guruswamy, Megha; Marimuthu, Murugan; Coll, Moshe
Abstract: BACKGROUND: Host plant resistance plays an important role in integrated pest management programs. Crop resistance assessments commonly focus on only a single dependent variable, such as larval survival/plant damage, which limits the ability to appreciate the impact of host plants on pest populations in the full sense. Therefore, we performed life‐table analyses for tomato leaf miner Tuta absoluta, on 19 Solanum lycopersicum genotypes and a wild Solanum habrochaites accession. These analyses assess the ability of the pest to attain a high population density on different tomato genotypes. Based on the resulting ranking of tomato resistance at the vegetative stage (45‐day‐old plants), we tested the resistance of six selected genotypes at the reproductive stage (4‐month‐old plants). RESULTS: T. absoluta performance was significantly inferior on vegetative‐stage S. habrochaites plants (LA 1777); time taken for the first instars to mine the leaves (5 ± 0.14 days), development time of early‐ and late‐stage larvae (8.8 ± 0.2 and 4.2 ± 0.2 days, respectively), pupal period (11.2 ± 0.58 days), and total developmental time (29.4 ± 0.83 days) were significantly longer, fecundity was significantly lower (18.66 ± 7.24 days), and the highest total mortality (63.33%) also recorded compared with other genotypes, resulting in the lowest net reproductive rate ( R 0 ) (11.20 ± 2.51). For the six selected genotypes, the ranking of plant resistance did not change between plants at the vegetative and reproductive stages. CONCLUSION: This study suggested that of 20 screened tomato genotypes, LA 1777 and EC‐620343 are the least suitable hosts for T. absoluta to establish fast‐growing populations, and thus can be employed in integrated T. absoluta management. © 2023 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : This study suggested that of the 20 screened tomato genotypes, LA 1777 and EC 620343 are the least suitable hosts for Tuta absoluta to establish fast‐growing populations, and thus should be employed in integrated T. absoluta population management programs.